NON-UNION AND RESORPTION OF EXTENDED TROCHANTERIC OSTEOTOMY AND MANAGEMENT USING MODULAR TAPERED STEM IN PATIENT WITH EXTENSIVE SURGICAL HISTORY - Onafowokan, Oluwatobi O; Singh, Amit; Patel, Kuntal (Journal of Ayub Medical College Abbottabad, 2023)
Extended trochanteric osteotomy is an invaluable technique for enhancing femoral exposure during revision total hip arthroplasty. Complications are rarely reported but may include non-union. Even rarer is the incidence of extended trochanteric osteotomy resorption. We present our experience using a modular tapered stem in managing a resorbed extended trochanteric osteotomy following revision total hip arthroplasty in a patient with extensive hip surgical history. Good surgical technique is important in the prevention and management of resorption. It is also important to identify high risk patients such as smokers or those with peripheral vascular disease. A long femoral stem prosthesis with diaphyseal fixation may help in dealing with proximal bone loss due to resorption of an extended trochanteric osteotomy, and avoids the need for allogenic bone graft.